Penerapan Algoritma Rail Fence Least Untuk Enkripsi Database Pada Aplikasi Rekrutmen Karyawan Baru Pada PT. Mukti Mandiri Lestari Berbasis Web - Silaban, Bahrum; Yanti Tusman; Rizky Vita Losi (Universitas Sari Mutiara Indonesia Medan, 2024)
Applying encryption to databases is a crucial step in maintaining data security, especially in applications that handle sensitive information such as the employee recruitment process. This research aims to implement the Rail Fence Least algorithm in database encryption in a web-based new employee recruitment application at PT. Mukti Mandiri Lestari. The Rail Fence Least algorithm was chosen because it has advantages in terms of speed and efficiency of data encryption and decryption. The implementation of this algorithm is expected to increase the security of prospective employee data from potential unauthorized access and misuse of information. Test results show that this algorithm is effective in securing data without significantly compromising application performance. Thus, implementing the Rail Fence Least algorithm is the right solution to improve database security in new employee recruitment applications at PT. Mukti Mandiri Lestari.